Comparison of physical fitness and quality of life between adolescents engaged in sports and those who are not - Ana Beatriz Pacífico; Edina Maria de Camargo; Valdomiro de Oliveira; Gislaine Cristina Vagetti; Thiago Silva Piola; Wagner de Campos (Universidade Federal de Santa Catarina, 2018)
Adolescence is conducive to implementing interventions that encourage healthy lifestyles, especially when there is involvement with sports. The aim of this study was to compare physical activity, physical fitness and quality of life perception of adolescents who practice and do not practice after-school sports. The sample consisted of 374 adolescents, 198 boys and 176 girls, with mean age of 16.35 ± 0.65 and 16.19 ± 0.67 years. The QAFA questionnaire was used to evaluate the level of physical activity and the Fitnessgram was used to evaluate physical fitness. The KIDSCREEN-52 was used to evaluate quality of life perception. One-way ANOVA was conducted for comparisons (p>0.05). Boys and girls who did not practice sports  presented lower levels of physical activity and physical fitness compared to those engaged in after-school sports and other type of regular physical exercise (p<0,01). Boys and girls engaged in after-school sports also presented higher scores for quality of life perception (p ≤ 0.01). Adolescents engaged in after- school sports showed higher levels of physical activity and better quality of life perception. Physical fitness components were better for adolescents engaged in after-school sports and for those engaged in other physical exercise modalities.